FLIGHT GUIDANCE AND CONTROL SYSTEMS OF CRUISE MISSILE FOR CRUISE AND TERMINAL PHASE - Fariz, Ahmad
Cruise missiles are one type of unmanned weapon used to attack a long-range target with a precise angle of impact. The flight in the cruise phase is carried out at low altitudes with the terrain following guidance system. In the terminal phase, the missile aims a specific point on the target. The cruise phase guidance system is supported by a stabilization system and a normal acceleration and an altitude tracking system. The guidance system for terminal phase is supported by the same tracking system but without altitude tracking system.